Tantangan dan Solusi dalam Penerapan Kurikulum Merdeka di SMP N 1 Kota Bengkulu - HK, M Nasron; Khair, Hanifah Khalishah; Khansa, Sherli Amirah; Topia, Anisa (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2025)
This research aims to analyze the impact of Islamic Religious Education (PAI) learning methods on student learning motivation at SMPN 12 Bengkulu City. The research method used is quantitative research with a descriptive approach. Data was collected through observation, questionnaires and interviews with PAI students and teachers. The research results show that varied learning methods, such as group discussions, interactive lectures, and technology-based approaches, have a positive impact on students' learning motivation. Factors that contribute to increasing learning motivation include active student interaction, teacher involvement in facilitating learning, and the use of innovative learning media. This research concludes that choosing the right learning method in PAI plays a significant role in increasing students' learning motivation.